ENHANCING UNIVERSITY STUDENTS’ WRITING SKILLS THROUGH GAMES - N.A.G‘opurova, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation. This article examines the effectiveness of game-based learning in developing writing skills among university students. As writing remains one of the most challenging productive skills for learners of English as a Foreign Language (EFL), instructors increasingly seek interactive and motivating techniques to support students' progress. Game-based activities offer opportunities for collaboration, creativity, and communicative practice, which help reduce anxiety and foster engagement. The study highlights several types of educational games, their pedagogical value, and practical applications in writing classes. The results indicate that integrating game elements—such as competition, rewards, problem-solving, and storytelling—significantly enhances learners’ motivation, language accuracy, and discourse organization. Pedagogical implications and recommendations for EFL teachers are discussed.